Analisis Komparasi Tafsir Al-Muyassar dan Tafsir Al-Jîlânî Terhadap Konsep Rûh Dalam Al-Qur’an - Irsyad Al Fikri Ys (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
This paper will reveal the concept of rûh in the Qur'an by comparing the interpretation of al-Muyassar and the interpretation of al-Jlânî. From the two interpretations, there are similarities in the style, namely Sufism. It was found that al-Muyassar's interpretation explained the verses of the Qur'an briefly and directly revealed the core meaning in the context of the interpreted verse so that it was easily accepted and understood by Muslims in modern times, while al-Jîlânî's interpretation explained the verse in great detail so that requires study to arrive at the level of understanding conveyed by the interpretation. The research method in this paper is descriptive analytical based on library research. The results of this study will reveal the concept of rûh in the Qur'an, namely in QS. al-Isra ': 85 rûh is defined by a substance that is united with the body and becomes the source of life, in the QS. al-Isra ': 85 is defined as the essence that comes from the light of Allah's form, in QS. al-Hijr: 29 and QS. as-Sajadah: 9 rûh is interpreted as an element that comes from the Essence of Allah SWT.